Heat Shock Protein 22 Attenuates Doxorubicin-Induced Cardiotoxicity via Regulating Inflammation and Apoptosis - Lan, Yin; Wang, Yi; Huang, Kun; Zeng, Qiutang (Frontiers in Pharmacology, 2020)
Background: The antitumor effect of Doxorubicin (DOX) is limited by its acute and chronic toxicity to heart, which causes heart injury. Heat shock protein 22 (Hsp22) is a protein proved to exert anti-apoptosis and anti-inflammatory effects in other diseases and physical condition. In this study we aim to explore whether Hsp22 could exert protective role during cardiac injury in response to DOX. Methods: The overexpression of Hsp22 was mediated via adenovirus vector, to clarify the role of Hsp22 in the cardiac injury caused by DOX. DOX-induced acute heart injury mouse model was established by single intraperitoneal injection of DOX (15mg/kg). Subsequently, cardiac staining and molecular biological analysis were performed to analyze the morphological and biochemical effects of Hsp22 on cardiac injury. H9c2 cells were used for validation in vitro. Results: Increase in expression level of Hsp22 was observed in DOX-treated heart tissue. Furthermore, cardiac-specific overexpression of Hsp22 showed reduced cardiac dysfunction, decrease in inflammatory response and reduction in cell apoptosis in injury heart and cardiomyocytes induced by DOX in vivo and in vitro. Moreover, the suppression of TLR4/NLRP3 was associated with the protective effect of Hsp22. Finally, the protective effect of Hsp22 cardiac function was almost abolished by overexpression of NLRP3 in DOX treated mice. Conclusion: In summary, Hsp22 overexpressing in heart could suppress cardiac injury in response to DOX treatment through blocking TLR4/NLRP3 activation. Hsp22 may become a new therapic method for treating cardiac injury induced by DOX in cancer patients.